Meningkatkan Kreativitas Siswa Dalam Proses Pembelajaran Dengan Menggunakan Model Generatif di Sekolah Dasar - Nandia Kiranti; Syafa Herdiani; Prihantini Prihantini (PT. ALHAFI BERKAH INDONESIA, 2023)
Increasing student creativity is one of the main goals in the learning process through the application of generative models in elementary schools (SD). This model is designed to help students develop creative skills and create an inclusive and innovative learning environment. Activities carried out during this process include, but are not limited to: Collaborative Learning: Generative models allow students to collaborate in groups, discuss ideas, and create innovative work. The use of generative learning models in elementary schools (SD) aims to increase student creativity in the learning process . This model provides opportunities for students to continue learning, develop creative skills, and create an inclusive and innovative learning environment. Several studies show that implementing generative learning models increases student creativity in various subjects, such as mathematics and dance practice. Apart from that, this model also aims to improve students' learning outcomes and problem solving skills. Therefore, the introduction of generative learning models can be an effective alternative for increasing student creativity in elementary schools. In the learning process using generative models, each stage must be carried out well to achieve the desired results. Increasing student creativity is one of the main goals in the learning process through the application of generative models in elementary schools (SD).